Efficacy and safety of combined piroxicam, dexamethasone, orphenadrine, and cyanocobalamin treatment in mandibular molar surgery - A.B. Barroso; V. Lima; G.C. Guzzo; R.A. Moraes; M.C. Vasconcellos; M.M. Bezerra; F.A.L. Viana; R.C.R. Bezerra; G.S.M. Santana; F.A. Frota-Bezerra; M.O. Moraes; M.E.A. Moraes (Brazilian Journal of Medical and Biological Research, 2006)
Third molar extraction is a common procedure frequently accompanied by moderate or severe pain, and involves sufficient numbers of patients to make studies relatively easy to perform. The aim of the present study was to determine the efficacy and safety of the therapeutic combination of 10 mg piroxicam, 1 mg dexamethasone, 35 mg orphenadrine citrate, and 2.5 mg cyanocobalamin (Rheumazin®) when compared with 20 mg piroxicam alone (Feldene®) in mandibular third molar surgery. Eighty patients scheduled for removal of the third molar were included in this randomized and double-blind study. They received (vo) Rheumazin or Feldene 30 min after tooth extraction and once daily for 4 consecutive days. Pain was determined by a visual analogue scale and by the need for escape analgesia (paracetamol). Facial swelling was evaluated with a measuring tape and adverse effects and patient satisfaction were recorded. There was no statistically significant difference in facial swelling between Rheumazin and Feldene (control group). Both drugs were equally effective in the control of pain, with Rheumazin displaying less adverse effects than Feldene. Therefore, Rheumazin appears to provide a better risk/benefit ratio in the mandibular molar surgery. Since the side effects resulting from nonsteroidal anti-inflammatory drug administration are a severe limitation to the routine use of these drugs in clinical practice, our results suggest that Rheumazin can be a good choice for third molar removal treatment.